Social TV : multiscreen content and ephemeral culture - Barker, Cory, 1988- (University Press of Mississippi, 2022)
"On March 15, 2011, Donald Trump changed television forever. The Comedy Central Roast of Trump was the first major live broadcast to place a hashtag in the corner of the screen to encourage real-time reactions on Twitter, generating more than 25,000 tweets and making the broadcast the most-watched Roast in Comedy Central history. The #trumproast initiative personified the media and tech industries' utopian vision for a multiscreen and communal live TV experience. In Social TV: Multiscreen Content and Ephemeral Culture, author Cory Barker reveals how the US television industry promised-but failed to deliver-a social media revolution in the 2010s to combat the imminent threat of on-demand streaming video. Barker examines the rise and fall of Social TV across press coverage, corporate documents, and an array of digital ephemera. He demonstrates that, despite the talk of disruption, the movement merely aimed to exploit social media to reinforce the value of live TV in the modern attention economy. Case studies from broadcast networks to tech start-ups uncover a persistent focus on community that aimed to monetize consumer behavior in a transitionary industry period. To trace these unfulfilled promises and flopped ideas, Barker draws upon a unique mix of personal Social TV experiences and curated archives of material that were intentionally marginalized amid pivots to the next big thing. Yet in placing this now-forgotten material in recent historical context, Social TV shows how the era altered how the industry pursues audiences. Multiscreen campaigns have shifted away from a focus on live TV and toward all-day "content" streams. The legacy of Social TV, then, is the further embedding of media and promotional material onto every screen and into every moment of life"--